Política agrícola en Costa Rica y su efecto sobre el campesinado. ¿Tendrá la educación "alguna vela en este entierro"? - Fernando Sáenz-Segura (Universidad Nacional, Costa Rica, 2002)
Agrarian policy, rural population and education are three issues which are combined in this study and examined in a particularly difficult context for small farmers in Costa Rica . Although the term agrarian policy refers to the ways in which the government proposes objectives and goals for the farm sector, and the methods to be used to reach them, the lack of defined policies is a political option in itself. This study describes the change from an aid-oriented development model to that of the free market, where the lack of a defined agrarian policy appears to be the norm. This has been particularly serious for the small farmers in Costa Rica, who were affected by the same agro-export bias policies as those applied to the large producers, with no adequate preparatory strategy. Most small farmers have suffered from economic exclusion and poverty for 20 years. This situation has endangered the existence of the social network in rural areas. The analysis is extended to cover the role assumed by education to the present time, and includes its implications in this process of change in the farm sector.